Ketahanan Isolat Bakteri Asam Laktat Indigenus Kombucha dan Dadih Terhadap Antibiotik - Jaya Sukarya, Ida Bagus; Pratiwi, I Desak Putu Kartika; Hapsari Arihantana, Ni Made Indri; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 4 (2021): Jurnal ITEPA, 2021)
Lactic Acid Bacteria must pass several tests to increase their potential as probiotics, one of which is to test their resistance to antibiotics. This study was aimed to determine the resistance of the indigenous lactic acid bacteria (LAB) isolates from kombucha and dadih against amoxicillin, tetracycline, and chloramphenicol, and measure their levels of resistance against amoxicillin, tetracycline, and chloramphenicol. There were 2 treatments that are done in this study such as the type of isolates, and the type of antibiotics used. LAB growth inhibition zones against antibiotics were tested using disk diffusion method and analyzed using quantitative descriptive method. Based on the result of this study, it was found that L. plantarum RN9, L. plantarum I MK2, and L. plantarum I ML7 had an intermediate resistance against amoxicillin, while all the isolates tested are resistant to tetracycline and chloramphenicol. L. pentosus MS21 had the most resistance against amoxicillin. L. plantarum I MK2 had the most resistance against tetracycline. and L. plantarum I ML7 had the most resistance against chloramphenicol.